Evaluation of the Independent Career Promotion and Income Earning While Studying Project for Junior High School Students at Bansunyoong School, under Nakhon Si Thammarat Primary Educational Service Area Office 1 - Nootong-In, Supattra; Rattanaphant, Thanatcha; Chairueng, Nopparat (Journal of Buddhist Education and Research (JBER), 2024)
This research applied the CSE Model to evaluate the system, planning, implementation, improvement, and acceptance of the project. The participants included one school administrator, two project coordinators, three homeroom teachers, 41 students, and 38 parents, selected through purposive sampling. The instruments used were questionnaires and interview guides, and data analysis involved percentage, mean, standard deviation, and content analysis. The findings revealed that the overall evaluation of the project system, planning, and implementation was rated at a high level. The general condition of the project received the highest mean score in system assessment, while curriculum and activity content ranked highest in planning. Similarly, the assessment and evaluation process scored highest in implementation. Weaknesses identified included time constraints and insufficient materials and equipment for activities. Suggested improvements included extending the training period, discussing budget allocation and procurement, and creating opportunities for the community to sample or provide feedback on products to enhance quality. The overall acceptance of the project also received the highest average score, with students demonstrating outstanding diligence, perseverance, and commitment to tasks assigned during the training.